Effect of gonadotropin releasing hormone and prostaglandin for improving reproductive efficiency in goats - Julliet (Department of Animal Reproduction, Gynaecology and Obstetrics, College of Veterinary and Animal Sciences, 2008)
With the objective of studying the effect of GnRH and prostaglandin for improving reproductive efficiency in goats the study was carried out at University Sheep and Goat Farm, Mannuthy using 42 cycling goats. Based on the behavioural and physiological changes associated with oestrum the goats were divided into two groups viz., Group I and Group II. Group I animals were those that exhibited pronounced oestrus signs and were divided into two subgroups namely Group IA and Group IB. Group II animals were those that exhibited weak oestrus signs and were divided into three subgroups namely Group IIA, IIB and IIC. Group IA animals were administered 0.0042 mg Buserelin (1 ml Receptal) a potent GnRH analogue on day 0, and Group IB served as the Control. Blood was collected prior to GnRH administration and breeding from all does. The mean duration of oestrum in Group IA and IB was 19.33 ± 0.45 and 33 ± 0.58 h respectively. The conception rate in Group IA and IB was 50 per cent and 66.66 per cent respectively. The serum P4 level on day 0 in does in Group IA and IB was 0.43 ± 0.05 ng/ml and 0.40 ± 0.05 ng/ml respectively. Group IIA and Group IIB does were treated as per the CO-Synch protocol (i/m inj. of 0.0042 mg of Buserelin (1 ml Receptal) on day 0, 125 µg cloprostenol (0.5 ml clostenol) on day 7; 0.0042 mg of Buserelin and mating on day 9) and prostaglandin protocol respectively (two intramuscular injections of 125 µg cloprostenol (0.5 ml clostenol) 11 days apart followed by mating at 72 and 96 h), while Group IIC served as the control. The oestrus response, oestrus onset interval, duration of oestrum and conception rate in Group IIA was 90.9 per cent, 47.6 ± 0.45 h, 24.5 ± 0.63 h and 40 per cent respectively. The oestrus intensity score of induced oestrus ranged from 0 to 13. The serum P4 level in pregnant and non pregnant does was not significantly different on days 0, 7 and 9 (P>0.05). The oestrus response, oestrus onset interval, duration of oestrum and conception rate in Group IIB was 81.8 per cent, 54 ± 1.006 h, 39.77 ± 1.54 h and 66.66 per cent respectively. The oestrus intensity scores in induced oestrus ranged from 0 to 13. The serum progesterone level in does that became pregnant and those that were non pregnant were not significantly different on day 0, 11, and at 72 and 96 h. In Group II C the duration of oestrum and pregnancy rates was 40 ± 0.91 h and 33.33 per cent respectively. Pregnancy diagnosis was done at three months of gestation by abdominal palpation and the accuracy of the method was 90.9 per cent. Mean gestation length was 146.03 ± 0.76 days. Litter size at birth in Group IA, IB, IIA, IIB and IIC was 2, 2, 2, 1.83 and 2 respectively. Average birth weight of kids was 2.35 ± 0.164 kg and the mean birthweight of male and female kid was 2.42 ± 0.98 kg and 2.28 ± 0.36 kg respectively. Thus from the present study, it can be concluded that :- 1. Administration of GnRH on the day of oestrum in animals exhibiting pronounced oestrus signs failed to improve conception rate when compared to the control. 2. In animals exhibiting weak oestrus signs both CO-Synch and double prostaglandin protocols resulted in higher conception rate when compared to control group. 3. The double prostaglandin protocol was found to be more efficient in improving conception rate in animals exhibiting weak oestrus signs.